Renewable energy for mitigating climate change - Stagner, Jacqueline A.; Ting, David S-K (CRC Press, 2022)
"Based on state-of-the-art science and technologies, this book disseminates the latest progress concerning the marriage between renewable energy and climate change, and examines the best practices to further utilize renewable energy for mitigation. It examines climate change from different renewable energy fronts by the respective experts from around the world. While high-level and in-depth technological advancements are judiciously presented, it also discusses the various forms of renewable energy and the associated technologies in consideration of the various perspectives of economy, availability, and societal implications in different regions"--